Early treatment of open diaphyseal tibia fracture with intramedullary nail versus external fixator in Tanzania: Cost effectiveness analysis using preliminary data from Muhimbili Orthopaedic Institute - Haonga Billy T.; Areu Mapuor M.M.; Challa Sravya T.; Liu Max B.; Elieza Edmund; Morshed Saam; Shearer David (SICOT-J, 2019)
Introduction: Open tibia fractures are some of the most common types of Orthopedics injuries in low- and middle-income countries (LMICs). In Tanzania, open tibia fractures are treated either conservatively by prolonged cast or surgically by external fixation (EF) or intramedullary nail (IMN) when available. The cost of treatment and amount of time patients spend away from work are major economic concerns with prolonged casting and EF. The goal of this study was to determine the cost effectiveness of IMN versus EF in the treatment of open diaphyseal tibia fractures at Muhimbili Orthopaedic Institute (Dar es Salaam, Tanzania). Methods: This is a prospective randomized control study conducted of patients with a closeable AO/OTA 42 open diaphyseal tibia fracture. The patients underwent surgical fixation with either IMN or EF at Muhimbili Orthopaedic Institute (MOI), and were followed up at 2, 6, and 12 weeks postoperatively. A micro-costing method was used to estimate the fixed and variable costs of IMN and EF of the open diaphyseal tibial fracture. Results: The mean total cost per patient was lower for the IMN group ($425.8 ± 38.4) compared to the EF group ($559.6 ± 70.5, p < 0.001), with savings of $133.80 per patient for the IMN group. The mean hospital stay was 2.72 ± 1.40 days for the IMN group and 2.44 ± 1.47 days for the EF group (p = 0.5). Quality-adjusted life years (QALYs) were 0.26 per patient for the IMN group and 0.24 in the EF group at 12 weeks (p = 0.8). Ninety-two percent of patients in the IMN group achieved fracture union versus 60% in the EF group at three months postoperatively (p = 0.03). Conclusion: IM nailing of a closeable open diaphyseal tibial fracture is more cost effective than EF. In addition, IM nailing has better union rates at three months compared to EF.